Reconstitution of maltose transport in Escherichia coli: conditions affecting import of maltose-binding protein into the periplasm of calcium-treated cells. - Brass, J M (1983)
The reconstitution of active transport by the Ca2+ -induced import of exogenous binding protein was studied in detail in whole cells of a malE deletion mutant lacking the periplasmic maltose-binding protein. A linear increase in reconstitution efficiency was observed by increasing the Ca2+ - concentration in the reconstitution mixture up to 400 mM. A sharp pH optimum around pH 7.5 was measured for reconstitution. Reconstitution efficiency was highest at 0 degree C and decreased sharply with increasing temperature. The time necessary for optimal reconstitution at 0 degree C and 250 mM Ca2+ was about 1 min. The competence for reconstitution was highest in exponentially growing cultures with cell densities up to 1 X 10(9)/ml and declined when the cells entered the stationary-growth phase. The apparent Km for maltose uptake was the same as that of wild-type cells (1 to 2 microM). Vmax at saturating maltose-binding protein concentration was 125 pmol per min per 7.5 X 10(7) cells (30% of the wild-type activity). The concentration of maltose-binding protein required for half-maximal reconstitution was about 1 mM. The reconstitution procedure appears to be generally applicable. Thus, galactose transport in Escherichia coli could also be reconstituted by its respective binding protein. Maltose transport in E. coli was restored by maltose-binding protein isolated from Salmonella typhimurium. Finally, in S. typhimurium, histidine transport was reconstituted by the addition of shock fluid containing histidine-binding protein to a hisJ deletion mutant lacking histidine-binding protein. The method is fast and general enough to be used as a screening procedure to distinguish between transport mutants in which only the binding protein is affected and those in which additional transport components are affected.